Answer:
The product is the difference of squares is ![$$\left(xy-9\right)\left(xy+9\right)={{x}^2}{{y}^2}-81$$](https://tex.z-dn.net/?f=%24%24%5Cleft%28xy-9%5Cright%29%5Cleft%28xy%2B9%5Cright%29%3D%7B%7Bx%7D%5E2%7D%7B%7By%7D%5E2%7D-81%24%24)
Step-by-step explanation:
Explanation
- The given expression is (x y-9)(x y+9).
- We have to multiply the given expression.
- Square the first term xy. Square the last term 9 .
![$$\begin{aligned}&(x y-9)(x y+9)=(x y)^{2}-(9)^{2} \\&(x y-9)(x y+9)=x^{2} y^{2}-81\end{aligned}$$](https://tex.z-dn.net/?f=%24%24%5Cbegin%7Baligned%7D%26%28x%20y-9%29%28x%20y%2B9%29%3D%28x%20y%29%5E%7B2%7D-%289%29%5E%7B2%7D%20%5C%5C%26%28x%20y-9%29%28x%20y%2B9%29%3Dx%5E%7B2%7D%20y%5E%7B2%7D-81%5Cend%7Baligned%7D%24%24)
Answer:
Answer
sqrt(108)
6 sqrt(3)
10.3923
I don't know which answer you want.
Step-by-step explanation:
- Drop a perpendicular from the top angle to the base.
- The base is cut into 2 equal parts.
- Each part is 12/2 = 6
- The perpendicular, as its name implies, meets the base at 90o.
- You can use the Pythagorean Theorem to find the height.
h^2 = side^2 - (1/2 b)^2
h^2 = 12^2 - 6^2
h^2 = 144 - 36
h^2 = 108
Take the square root of both sides
h = sqrt(108)
h = sqrt(2*2 * 3 * 3 * 3)
h = 2 * 3 sqrt(3)
h = 6sqrt(3)
h = 6 * 1.7321
h = 10.3923
Answer:
x=3
Step-by-step explanation:
Vertical angles are equal so
<A = <B
7x+2 = 4x+11
Subtract 4x from each side
7x+2-4x = 4x+11-4x
3x+2 =11
Subtract 2 from each side
3x+2-2 = 11-2
3x = 9
Divide by 3
3x/3 = 9/3
x=3
Answer:
Step-by-step explanation:
you have to minus 6.50 by 2 and you get the answer the anwser is 4.5
9514 1404 393
Answer:
(c) -3/4
Step-by-step explanation:
Subtracting a positive number moves you to the left on the number line. Subtracting a negative number moves you in the opposite direction, to the right.
Here, we start at -2 1/2 = -5/2, and we move 1 3/4 = 7/4 to the right from there. Each mark on this number line is 1/4 unit, so we move 7 marks. The results is ...
-2 1/2 -(-1 3/4) = -5/2 +7/4
= -10/4 +7/4 = -3/4